Gene doping: An overview and update (Play true, 2007)
Interview with expert Prof. Theodore Friedmann, professor of pediatrics and director of the gene therapy program at the University of California, San Diego (U.S.). Prof. Friedmann is head of WADA's panel on gene doping and shares his thoughts on the current state of gene therapy and its implications for doping and sport. He answers the following questions: - How have recent advances in genetics impacted the world of sport? - Do you believe that gene doping is happening right now? - In terms of developing a detection method for gene doping, how high of a priority is this for the anti-doping community? - What kind of outcomes has the research provided so far? - At the December 2005 Gene Doping Workshop, experts stated, in the Stockholm Declaration that "gene transfer for the purpose of therapy remains a very immature and experimental field of human medicine." Have there been any significant developments in gene therapy since then that would change the outlook for gene doping? - You also stated that scientific progress "suggests that new detection methods are likely to emerge, which will help to keep sport untainted by gene doping methods." Is this true?